Complex estimation of development of power capabilities of students of higher educational establishments - V.N. Sergienko (Physical Education of Students, 2013)
The features of development of complex of brief variant of development of power capabilities of students of basic educational separation are considered. In research took part 800 youths in age 17-20 years. The improvement of indexes is shown in test exercises (figure force; bendings and unbending of hands after 20 with; raising of trunk, hands on a breast) within the limits of 5,2-12,3%. The results of complex estimation of power capabilities are exposed to on to the 12-ball to the sigmoid scale in every age group of youths. It is set that a high-quality estimation fine is not fixed, estimation satisfactorily - within the limits of 52-62%, unsatisfactorily - within the limits of 28,5-31,5%, well - within the limits of 10-15% and badly - within the limits of 0,5-1,5%. Recommended on employments on physical education in a greater degree to spare attention physical exercises on development of speed force of students.